MENINGKATKAN KETERAMPILAN MENYETRIKA PAKAIAN ANAK TUNAGRAHITA SEDANG - Saptunar - - (Jurnal Penelitian Pendidikan Khusus, 2012)
The purpose of this study are: 1) Describe the process of improving the implementation of learning in improving the skills of ironing clothes with training methods and 2) Prove that if the training methods can enhance the skills of ironing clothes the child is a class VII in Tunagrahita SMPLB Pasaman Panti. This type of study is classroom action research (classroom action research) with two cycles are performed in collaboration with colleagues. Data obtained through observation and tests. Then analyzed qualitatively and quantitatively. The results showed that 1) the process of learning to improve skills training methods ironing done in two cycles. Cycle I made seven (7) meetings and the second cycle of five (5) meetings. Each cycle begins with the planning, implementation (initial activity, core and end), observation, and analysis and reflection. 2) The result of learning to practice the method of ironing skills are improved. It is proved: before treatment (assessment) the child's ironing skills: FN by (35%), RK (30%) and WT (25%). I cycle an increase in the skills of FN (80%), by RK (65%) and the WT is (60%). Whereas in the second cycle is increasing, where FN into (95%), RK (90%) and WT (85%). Suggested in the schools, teachers and researchers can use the method further for training in other skills to children Tunagrahita being.